2015
DOI: 10.14260/jemds/2015/1738
|View full text |Cite
|
Sign up to set email alerts
|

“Botox: Tales Beyond Beauty”

Abstract: BOTOX is a trade name for "botulinum toxin", which comes in the form of a purified protein. There are seven distinct serotypes of botulinum toxin, viz., A, B, C, D, E, F, and G. Botulinum toxin A is the most commonly used form. The toxin inhibits the release of acetylcholine (ACH), resulting in temporary reduction of tone in the injected muscle. Apart from common cosmetic treatment for lines and wrinkles on the face, it has some therapeutic uses in diseases like temporomandibular disorders, bruxism, periodonta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…The fundamental aspects in facial aesthetics are mouth and teeth. 28 Botox is non-invasive procedure Brin et al (1987) In Randomized controlled trials concluded botulinum bene icial for chronic daily headaches and chronic migraines Verma et al (2015) 3 months Yiannakopoulou (2015) which has reversible effects, conservative, nonsurgical, treatment modality to achieve optimum aesthetics. It becomes easy for the dentists to learn the injecting techniques as they are already aware about the anatomical landmarks to be considered while managing the cases during administration of local anaesthesia thus patients are at ease and comfort.…”
Section: Resultsmentioning
confidence: 99%
“…The fundamental aspects in facial aesthetics are mouth and teeth. 28 Botox is non-invasive procedure Brin et al (1987) In Randomized controlled trials concluded botulinum bene icial for chronic daily headaches and chronic migraines Verma et al (2015) 3 months Yiannakopoulou (2015) which has reversible effects, conservative, nonsurgical, treatment modality to achieve optimum aesthetics. It becomes easy for the dentists to learn the injecting techniques as they are already aware about the anatomical landmarks to be considered while managing the cases during administration of local anaesthesia thus patients are at ease and comfort.…”
Section: Resultsmentioning
confidence: 99%
“…Estudos recentes confirmam correlações positivas entre estresse, depressão e doença periodontal, demonstrando ligações convincentes entre depressão / estresse e perda dentária; estresse / depressão e negligência da higiene oral; e elevados níveis de cortisol e profundidade da bolsa / perda do dente. Estes estudos apoiam firmemente ambos os mecanismos biológicos e comportamentais para esta conexão perio-sistêmica (LACOPINO, 2009;VERMA et al, 2015).…”
Section: Tratamento Com Toxina Botulínica Em Pacientes Com Defeitos E...unclassified
“…And 0.9 milligrams of sodium chloride in a sterile, vacuum dried conformation unaccompanied by any preservative. 7…”
Section: Contents Of the Vialmentioning
confidence: 99%